1995
DOI: 10.1086/187756
|View full text |Cite
|
Sign up to set email alerts
|

A supernova at Z = 0.458 and implications for measuring the cosmological deceleration

Abstract: We have begun a program to discover high-redshift supernovae (z ≈ 0.25-0.5), and study them with follow-up photometry and spectroscopy. We report here our first discovery, a supernova at z = 0.458. The photometry for this supernova closely matches the lightcurve calculated for this redshift from the template of well-observed nearby Type Ia supernovae. We discuss the measurement of the deceleration parameter q 0 using such high-redshift supernovae, and give the best fit value assuming this one supernova is a no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 12 publications
2
101
0
Order By: Relevance
“…The spectroscopic capabilities of the available 4m telescopes were marginal for the faintness of the objects (Nørgaard-Nielsen et al 1989, Hansen et al 1989, Schmidt et al 1998, Riess et al 1998. A large project to search for distant SNe Ia was initiated in the early 1990s in Berkeley (Perlmutter et al 1991) and yielded first results on seven objects (several without spectroscopy and insufficient colour coverage Perlmutter et al 1995). As a result the inferred cosmology was not correct (Perlmutter et al 1997).…”
Section: The Expansion History Of the Universementioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopic capabilities of the available 4m telescopes were marginal for the faintness of the objects (Nørgaard-Nielsen et al 1989, Hansen et al 1989, Schmidt et al 1998, Riess et al 1998. A large project to search for distant SNe Ia was initiated in the early 1990s in Berkeley (Perlmutter et al 1991) and yielded first results on seven objects (several without spectroscopy and insufficient colour coverage Perlmutter et al 1995). As a result the inferred cosmology was not correct (Perlmutter et al 1997).…”
Section: The Expansion History Of the Universementioning
confidence: 99%
“…The following years saw the emergence of vastly improved search techniques, the advent of 8m and 10m telescopes -greatly improving the quality of the spectroscopic confirmations, refined analysis methods taking many contaminating effects into account and the delivery of a surprise. With the proof of concept from the early searches the new projects, the Supernova Cosmology Project (Perlmutter et al 1995, Knop et al 2003, Hook et al 2005) and the High-z Supernova Search Team (Schmidt et al 1998, Riess et al 1997, Garnavich et al 1998a,b, Riess et al 2000, Coil et al 2000, Tonry et al 2003, Williams et al 2003, Clocchiatti et al 2006), started to provide astonishing evidence that the distant SNe Ia appeared fainter than predicted in a massless, empty universe. Early criticism of these results concentrated on difficulties with photometric accuracy of the faint sources, the treatment of the dust absorption in the host galaxy of the supernova, possible secular evolution of the supernovae over time, uncertainties in the normalisation of the peak luminosity of the SNe Ia and the, at the time still fairly small, sample size of distant objects, which could lead to sample biases or Malmquist effects (see Leibundgut 2001 for a summary of these early problems).…”
Section: The Expansion History Of the Universementioning
confidence: 99%
“…The SCP published the initial result (Perlmutter et al 1995a), based on a single object, SN 1992bi at z = 0.458: Ω M = 0.2 ± 0.6 ± 1.1 (assuming that Ω Λ = 0). The SCP's analysis of their first seven objects (Perlmutter et al 1997) suggested a much larger value of Ω M = 0.88±0.6 (if Ω Λ = 0) or Ω M = 0.94 ± 0.3 (if Ω total = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the pioneering work of Norgaard-Nielsen et al (1989), whose goal was to find SNe in moderate-redshift clusters of galaxies, the SCP (Perlmutter et al 1995a(Perlmutter et al , 1997) and the HZT (Schmidt et al 1998) devised a strategy that almost guarantees the discovery of many faint, distant SNe Ia "on demand," during a predetermined set of nights. This "batch" approach to studying distant SNe allows follow-up spectroscopy and photometry to be scheduled in advance, resulting in a systematic study not possible with random discoveries.…”
Section: 1mentioning
confidence: 99%
“…High-redshift supernova searches have been proceeding since the late 1980's (Norgaard-Nielsen et al 1989;Couch et al 1989;Perlmutter et al 1995Perlmutter et al , 1997Perlmutter et al , 1998Perlmutter et al , 1999Schmidt et al 1998;Riess et al 1998;Tonry et al 2003;Knop et al 2003;Riess et al 2004). Particularly since the discovery of the accelerating expansion of the Universe, the high-redshift supernova methodology for measuring cosmological parameters has been critically scrutinized for sources of systematic uncertainty.…”
Section: Sources Of Systematic Uncertaintymentioning
confidence: 99%